The Effect Of E-Marketing With Aisas Model (Attention , Interest, Search, Action , Share) On Investment Decisions In Fintech Syariah - Adinda Dian Ramadhani; Abdi Triyanto; Iqbal Fadli Muhammad (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2019)
This study aims to examine the effect of E-marketing with the AISAS model on investment decisions. This research using quantitative research. Data was obtained by distributing online questionnaires to 30 respondents, who had or were investing in registered Islamic Fintechs in the Financial Services Authority (OJK). The sampling technique in this study is purposive sampling, while the Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach is using a data analysis technique. Data is processed using PLS 3.2.8. Based on the results of data analysis, the Attention variable has a significant effect on the Interest variable. Also, the Interest variable has a significant effect on the Search variable. Then, the Search variable has a significant effect on the Action variable, while the Action variable has not a significant effect on the Share variable. The Share variable has not a significant effect on investment decisions.